GIS-material for the archaeological project: Pottery in Kimstad - Swedish National Heritage Board, UV Öst (Uppsala University, 2014)
The information in the abstract is translated from the archaeological report:
Norrköping municipality is working on a local plan concerning the construction of a new commuter train station in Kimstad, Kimstad parish. The archaeological field work was performed in October 2004 and April 2005. Within the area of Object III and IV (possible archaeological sites) nothing of archaeological interest was found. Within Object II, a stone packing with fire cracked stones containing prehistoric pottery was discovered. The feature is understood to represent the outskirts of a settlement and/or a burial area. No further surveying was necessary after this feature had been found and no archaeological measures were thus taken within Object V. If the area is to be developed, a field evaluation of the newly found archaeological remains and a complementary assessment of Object V is suggested.

Purpose:

The information in the purpose is translated from the archaeological report:
The purpose of the archaeological assessment was to determine whether or not the development area contains any archaeological remains and to document and, if possible, date any remains found.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
Norrköpings kommun arbetar med detaljplan inför byggande av ny pendelstation i Kimstad, Kimstads socken, Norrköpings kommun. Fältarbetet har genomförts i oktober 2004 och april 2005. Inom Objekt III och IV påträffades inget av antikvariskt intresse. Inom Objekt II hittades dock en skärvstenspackning med förhistorisk keramik, vilket bedöms representera utkanten på ett boplats- och/eller gravområde. Då denna lämning påträffades beslöts att vidare utredning inte var nödvändig. Inga arkeologiska insatser gjordes därför inom Objekt V. Skulle exploatering bli aktuell föreslås dels en förundersökning av det nypåträffade fornlämningsområdet samt en kompletterade utredning inom Objekt V.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Syftet med den arkeologiska utredningen är att konstatera om exploateringsområdet innehåller fornlämningar eller ej samt att dokumentera och om möjligt tidsbestämma anläggningar och fynd.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: Keramik i Kimstad
Keywords: stone age; stenålder; Bronze Age; bronsålder; Iron Age; järnålder; HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi